The effect of biotic and abiotic elicitors on biomass and saponin production of secondary root cultivated in shake flasks Panax vietnamensis adventitious root - Linh, Nguyễn Thị Nhật; Tùng, Hoàng Thanh; Lộc, Nguyễn Hoàng; Nhựt, Dương Tấn (Vietnam Journal of Biotechnology, 2018)
Panax vietnamensis Ha et Grushv. is an endemic ginseng of Vietnam which has highly nutraceutical, medicinal and comercial values. Many its special saponins provide resistance to stress, disease and exhaustion. In this study, the biotic elicitors (yeast extract and chitosan) at concentrations from 50 – 200 mg/l and abiotic elicitors (jasmonic acid, abscisic acid and salicylic acid) at concentrations from 50 – 200 µl/l were used to evaluate the possibility of increasing secondary root’s biomass and saponin in Panax vietnamensis adventitious root cultures. This cultures were maintained on Innova 2100 shaker shaker plantform at a speed of 100 rpm, and its modified MS medium (NH4+/NO3-: 7.19/18.5 mM/mM) were supplemented with 7 mg/l IBA, 0.5 mg/l BA and 3% sucrose. Results after 56 days of cultured showed that most elicitors significantly reduced dry biomass of secondary roots as compared to control (exception the addition of 50 – 100 mg/l yeast extract or 50 µl/l salicylic acid). However, all elicitors increased saponin-accumulation, and abiotic elicitor is more effective saponin-accumulation than those biotic elicitors. Jasmonic acid obviously gave the best results; with total amount of 3 saponins at 150 µl/l, Rg1 at 100 µl/l, Rb1 at 50 µl/l and MR2 at 200 µl/l and Rg1 (3.22%), significantly higher than other concentration of elicitor. However, for accumulating saponins and developing secondary root, 150 mg/l YE is the most real effective in all elicitors (0.88 mg)